An Open Label Prospective Randomized Trial to Compare the Efficacy of Coal Tar-Salicylic Acid Ointment Versus Calcipotriol/Betamethasone Dipropionate Ointment in the Treatment of Limited Chronic Plaque Psoriasis - Khandpur, Sujay (Indian J Dermatol, 2014)
BACKGROUND: Chronic plaque psoriasis is a common papulosquamous skin disorder, for which a number of topical agents are being used including coal tar, topical steroids and more recently topical calcipotriol/betamethasone dipropionate. There is no study comparing purified coal tar preparation with calcipotriol/betamethasone dipropionate ointment in limited chronic plaque psoriasis. AIMS AND OBJECTIVES: A prospective randomized open label controlled trial to compare the efficacy and safety of topical application of coal tar-salicylic acid ointment with calcipotriol/betamethasone dipropionate ointment applied once at night for 12 weeks for the treatment of limited chronic plaque psoriasis. MATERIALS AND METHODS: A total of 62 patients of limited chronic plaque psoriasis (body surface area <10%) were randomized into two treatment groups: Group A received topical application of 6% coal tar with 3% salicylic acid ointment and Group B received calcipotriol/betamethasone dipropionate, once at night for 12 weeks. Results were assessed based on psoriasis area severity index (PASI) scores and patient global assessment (PGA) at each visit. RESULTS: Mean PASI was significantly lower at week 2 (P = 0.01) and week 4 follow-up (P = 0.05) and the mean reduction in PASI was significantly higher at week 2 (P = 0.02) with calcipotriol/betamethasone than coal tar-salicylic acid, but this difference was not sustained at subsequent follow-up visits. Similarly, PGA scores at weeks 2 and 4 were significantly lower with calcipotriol/betamethasone dipropionate ointment (P = 0.003 and P = 0.007 respectively). There was no significant difference in any parameter during subsequent follow-up visits or at the end of the treatment phase (12 weeks). CONCLUSION: Topical nightly application of calcipotriol/betamethasone dipropionate ointment leads to an initial, more rapid reduction in disease severity, but the overall outcome parameters are comparable in the two treatment groups.